Clasificación de lagos someros pampeanos mediante imágenes LandsatTM - Dukatz, F. (2006)
Under normal hydro-meteorological conditions, lagoons cover up to 2,000,000 of the pampas territory, distributed in more than 2,000 permanent lacunar bodies. They contribute significantly to the life quality of their inhabitants and they constitute a potential source of environmental, economic and recreational resources. Several studies in different lagoons in different temporal periods have been developed in the province of Buenos Aires. They responded in an optimum way to the original goals, but they are barely valid when looking for dynamic spatial and temporal patterns in the lagoons, involving the use of the support basin. The use of remote sensors has proved effective in collecting the information needed to evaluate the quality of water bodies, to allow the search of temporal and spatial patterns, and to link lagoon water quality data with the characteristics of land use. We propose a proce dure for previously normalized satelital image analysis that will allow a classification of the lagoons based on their optical properties, conditioned by the contents of suspended inorganic solid matter and algal biomass. The results will be compared to samples in the field and spatially extrapolated. They will be used to propose alternative management methods jointly with some local decision makers.